Self-development teaching module - Ali, Dayana Farzeeha (2015)
The new transformation of technical and vocational education has led to changes in the aspect of facilities, curriculum and teaching materials being used in Vocational Colleges. Nowadays, the teaching and learning process at Vocational Colleges is based on module. Due to the absence of standard academic module, novice teachers are required to develop modules for the purpose of teaching and learning and this scenario has created many problems. Novice teachers lack the skills to develop or produce teaching notes. Furthermore, they depend too much on handouts or textbooks given by the Ministry of Education as their teaching resources and students exercises. Some teachers take the initiative to utilise the internet as to avoid the need to produce own materials. Therefore, this effort was carried out in view of the strong demand for the development of modules, particularly for Vocational Colleges in order to overcome the issue of lack of standardized teaching materials for technical and vocational subjects taught at the colleges. In addition, the task provided students with the exposure and experiences in developing teaching modules which should give them many advantages as future teachers. Hence, applying the development of teaching module in the assignments of undergraduate education students can enhance their skills in developing modules which is useful especially for those who will be teaching at Vocational Colleges. Consequently, the integration of developing self-development teaching modules as part of the assignments for Faculty of Education undergraduate students has given them the skills they need to become competent technical and vocational teachers.